Islamic Boarding School Discourse: Analysis Of Kiai's Attribution To Muslim Woman - Wahidah, Finadatul (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Muslim women in this study are the clothes they wear. Muslim women's clothes continues to develop, many new trends emerge. Fashion show activities, artists involved in Muslim fashion trends, to shopping centers that provide various models of Muslim clothing. The diversity of Muslim styles is a new phenomenon that requires specific Islamic studies to provide objective observations to enlighten Muslims in living life. Islamic studies, one of which was born from the role and contribution of pesantren. Pesantren is the oldest Islamic educational institution in Indonesia, and Kiai, through his pesantren, always takes part in setting policies in pesantren. The movement and role of the Kiai are not only given to the pesantren he leads but also to the phenomena that occur in the community outside the pesantren. For example, the trend of Muslim fashion among women. The focus of this research is 1) What is the process of forming the kiai’s attribution to Women's Clothes?; 2) What is the model of the kiai’s attribution to Women's Clothes?. And as for the purpose of this study is to analyze the process of forming the kiai’s attribution to Women's Clothes; To analyze the attribution model of the kiai’s attribution to Women's Clothes. The research method used is a qualitative research method, and the type of research used is phenomenology. This research uses interview, observation, and documentation research techniques. The results of this study are the kiai's attribution to women's clothing is the kiai's perception of the phenomenon of Muslim Women's Clothes. 1) The process of forming the kiai's attribution, starting with the phenomena that occurred in Jember, was then interpreted based on the yellow book. The attribution of the Kiai states that there is a standard to cover the aurat. They agree on the obligation to cover the genitals (Satrul Aura); 2) The kiai's attribution model regarding Women's Clothes is moderate and pivots on the principle of covering aurat and not rejecting current fashions and trends. Tolerance attitude. The kiai's attribution model is based on sources of the Islamic law that form a collective agreement and form a sub-culture. The most important principle underlying the kiai's attribution is to live in harmony and mutual respect—tolerance between those who wear hijab and those who do not become the concentration of the Kiai. Keywords: Kiai’s Attribution, Muslim Women